Historicity of Vedic and Ramayan eras : scientific evidences from the depths of oceans to the heights of skies - Saroj Bala (Institute of Scientific Research on vedas, 2012)
Papers presented at the National Seminar on Scientific Dating of Ancient Events Before 2000 BC, held at New Delhi during 30-31 July 2011.